Pengaruh pemberian campuran fermentasi ampas tahu dan dedak padi dalam ransum terhadap performa bebek pedaging hibrida - Andrea Surya; Sari Suryanah; Nilawati Widjaya; Hilman Permana (University of Insan Cendekia Mandiri, 2021)
The study aimed to determine the effect of giving a mixture of fermented tofu dregs and rice bran in the ration on the optimal performance of hybrid ducks. The research has been held for 35 days from 22 July 2020 to 25 August 2020, located at Reungas Village, Jagabaya Village, Cimaung District, Bandung Regency, West Java Province. The research was carried out experimentally with a completely randomized design (CRD), consisting of four treatments, namely P0 (giving basal ration 100%), P1 (giving basal ration 80% + fermented tofu dregs 10% + fermented rice bran 10%), P2 (giving basal ration 70% + fermented tofu dregs 15% + fermented rice bran 15%), and P3 (giving basal ration 60% + fermented tofu dregs 20% + fermented rice bran 20%). Each treatment was repeated 5 times and each repetition consisted of 5 hybrid ducks. The observed variables were ration consumption, body weight gain and ration conversion. The data obtained were analyzed using variance (ANOVA), if there was an effect of treatment followed by Duncan's Multiple Range Test. The results showed that the mixture of fermented tofu dregs and rice bran each 20% in the ration could produce optimal performance with ration consumption of 3,042.49 g/ tail, body weight gain of 1,671.88 g/ tail, and ration conversion 1.79.